Airflow obstruction case finding in community-pharmacies: A novel strategy to reduce COPD underdiagnosis. Issue 4 (April 2015) - Castillo, D.; Burgos, F.; Guayta, R.; Giner, J.; Lozano, P.; Estrada, M.; Soriano, J.B.; Flor, X.; Barau, M.; Casan, P.; ,
Summary: Background: Community pharmacies (CP) have access to subjects at high-risk of suffering Chronic Obstructive Pulmonary Disease (COPD). We investigated if a COPD case finding program in CP could be a new strategy to reduce COPD underdiagnosis. Methods: Prospective, cross-sectional, descriptive, uncontrolled, remotely supported study in 100 CP in Barcelona, Spain. Pharmacists were trained in a four-day workshop on spirometry and COPD, and each was provided with a spirometer for 12 weeks. The program included questionnaires and forced spirometry measurements, whose quality was controlled and monitored by web-assistance. Findings: Overall 2295 (73.5%), of 3121 CP customers invited to participate in the program accepted, and 1.456 (63.4%) were identified as "high risk" for COPD using the GOLD questionnaire. Only 33 could not conduct spirometry, and a pre-bronchodilator airflow limitation (FEV1 /FVC ratio <0.7) was confirmed in 282 (19.8%); 244 of these were referred to their primary care (PC) physician for further diagnostic and therapeutic work-up, but only 39 of them (16%) fed-back this information to the pharmacist. Clinically acceptable quality spirometries (grade A or B) were obtained in 69.4% of the cases. Conclusion: This study shows that adequately trained and supported community pharmacists can effectively identify individuals at high risk of having COPD and can thus contribute to ameliorate underdiagnosis in this disease. Links between PC and CP should be improved to achieve a useful program.